COMMUNITY EMPOWERMENT THROUGH ERGONOMICS TRAINING WITH LOCAL WISDOM ORIENTED TO IMPROVE QUALITY OF SCULPTOR HEALTH IN THE PELIATAN VILLAGE, UBUD, GIANYAR, BALI-INDONESIA - Sutajaya, I Made (BALI MEDICAL JOURNAL, 2014)
Background: Until recently, data applied for reference of Balinese workers in their work stations and  processes, including anthropometric data still applying secondary data source from literature review.  This was probably inappropriate due to different size, since the literature data generally on the basis of  western size of anthropometry. The objective of this research, therefore, was to establish community  empowerment through ergonomics training with local wisdom oriented to improve the sculptor health  care quality and productivity. Ergonomics training through workshops conducted with a systemic,  holistic, interdisciplinary, and participatory (SHIP) approach. The training is done to make people  aware of the work as a sculptor that is very important to apply ergonomics in the workplace. The  results showed that ( a) participants judge that ergonomics workshop can open their insights about the  importance of the application of ergonomics in the workplace, (b) work equipment is not in  accordance with sculptor anthropometric, (c) inadequate working conditions, because the workers  were exposed to noise working tool more than 80 decibel and the room temperature exceeds 34OC  and work a lot of cockroaches and rats roam, and (d) the data of sculptor health quality is very poor,  increase the workload at about13.5 %, musculoskeletal complaints at about 41.3 % , and fatigue at  about 46.8 % ( p < 0.05 ) between before and after working. That means the work is very necessary  sculptor redesigned in order to achieve comfort, safe, healthy, effective, and efficient of working  conditions. It can be concluded that the ergonomics training with local wisdom oriented is required in  an effort to implement the principles of ergonomics to achieve adequate health care quality sculptors  and maximum productivity.
Keywords: community; empowerment; ergonomics; indigenous; health care quality.